PENGUATAN PENDIDIKAN KARAKTER (PPK) DALAM BUKU NIHONGO KIRAKIRA 1 SEBAGAI BAHAN AJAR BAHASA JEPANG UNTUK SISWA SMA - Nurica Virdaus (Omiyage : Jurnal Bahasa dan Pembelajaran Bahasa Jepang, 2022)
This research is motivated by an awareness of how important it is to strengthen character education for students, and teaching materials are one of the notable things in shaping character. The objective of this study was to describe the character values contained in Nihongo Kirakira 1 and its conformity with the PPK competency standards in the 2013 Curriculum. This research is qualified as descriptive qualitative research. The data used in this research were analyzed using content analysis methods. The results of this study indicate that the character values in Nihongo Kirakira 1 are religious, nationalism, independence, mutual cooperation, and integrity. The mutual cooperation character was found 12 times and has 5 sub-character values, independent was found 11 times has 3 sub-character values, integrity was found 9 times and has 3 sub-values, nationalism was found 7 times and has 2 sub-values, religious was found 6 times by bringing up 3 sub-character values. Therefore, this book has complied with the PPK competency standards in the 2013 Curriculum, so it is suitable to be used as teaching material in Japanese language learning in senior high schools and become a guide in instilling character values for students, especially Japanese language learners.